Simulation of adaptive gain control via 2-D lookup table for isolated hybrid micro-grid system - Ekhlas Mhawi Thajeel; Mazin Mustafa Mahdi; Abu Zaharin Ahmad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper presented a smartness 2-D lookup table (2-DLT) control by means of adaptation gain to develop a frequency controller and facilitate the power-sharing requirements in an isolated micro-grid system. This intelligence of an expert controller adopts the scale of adaptation gain for estimating control design. Synchronous power generators are commonly used to provide power to distant and isolated regions where grid expansion is expensive due to economic and technical constraints. Load frequency control (LFC) technology challenges to guarantee the reliability and stability regarding the system. It is known that conventional control methods are unreliable due to frequency variation and sudden changes in the load or failure generation. Traditional control and criteria may not be appropriate for the new structural networks, such as micro-grid. In this work, the performance of the proposed 2-DLT controller is examined and compared to the classical proportional integral (PI) controller and artificial neural network (ANN). The simulation system is implemented and tested using MATLAB/Simulink.